Socio-cultural factors and international competitiveness - Apsalone, Madara; Šumilo, Ērika (Business, Management and Economics Engineering, 2015)
Socio-cultural factors – shared values, norms and attitudes are significant, but less acknowledged sources of international competitiveness. Previous studies have found socio-cultural factors positively affecting various aspects of international competitiveness – entrepreneurship, innovation, productivity and international cooperation. These factors are more sustainable and less affected by external environment changes in comparison with the traditional factors. Socio-cultural factors provide an opportunity to develop competitiveness strategies based on unique advantages. This research aims to explore the impact of socio-cultural factors on international competiveness in small, open economies. Analysing relationship between 400 socio-cultural indicators and competitiveness indicators such as productivity, economic development, business and government efficiency, innovation capacity and infrastructure in 37 countries, six socio-cultural factors have emerged: Collectivism and Hierarchy; Future, Cooperation and Performance Orientation, Self-expression, Monochronism and Rationality, Economic Orientation and Social structure. The first factor – Collectivism and Hierarchy – tends to reduce the international competitiveness; the other five affect it positively.